Development of Project-Based Integral Calculus Teaching Materials Assisted by Geogebra Applications in Integral Calculus Courses - Elwan Stiadi; Ari Putra; Diah Selviani (Universitas Bengkulu, 2026)
Integral Calculus is a compulsory course in the Mathematics Education Study Program, Faculty of Teacher Training and Education, University of Bengkulu. The main focus of this course is to introduce students to the basic concepts and techniques in integral calculus. By studying Integral Calculus, students are also expected to hone their analytical, critical, and creative thinking skills in solving various problems involving integral concepts. To hone students' analytical, critical, and creative thinking skills, projects can be implemented in their learning. The design and implementation of projects in Integral Calculus can be done using the Geogebra application. However, currently available Integral Calculus teaching materials only contain materials and problems. This makes learning less interesting and makes students less active in class. This research aims to help overcome the challenges often associated with complex and abstract mathematical concepts and provide students with the opportunity to deepen their understanding of Integral Calculus concepts in a more active way. The subjects of this study were third-semester students of the Mathematics Education Study Program, Faculty of Teacher Training and Education, University of Bengkulu, taking the Integral Calculus course in the 2024/2025 academic year. This study applied the 4-D model: define, design, develop, and disseminate. Data collection methods used in this study were observation, interviews, recording, and questionnaire distribution. Furthermore, the data analysis techniques used were the validity and feasibility of the teaching materials through validation sheets and practicality sheets. The validation sheet was used to measure the validity of the content and language in the teaching materials, while the practicality sheet assessed the ease of use of the teaching materials in terms of presentation, language, and visual representation. The results of this study are valid and practical teaching materials. In addition, the results of this study will be realized in the form of teaching materials with ISBN numbers, and there will be additional results in the form of IPR.